Strategies for enhancing financial literacy in Indonesia - Maemunah, Sari (Privietlab, 2022)
This study provides a comprehensive analysis of financial literacy in Indonesia, identifying critical challenges and exploring effective strategies to improve financial education across the nation. Despite the growing importance of financial literacy in today's economic landscape, Indonesia faces lower rates of financial knowledge compared to global averages, with significant disparities across different demographic groups. Through a literature review approach, this research examines the current state of financial literacy, evaluates the effectiveness of existing educational programs, and proposes innovative solutions to bridge the knowledge gap. The findings highlight the potential of integrating financial education into national curricula and leveraging digital technologies to expand access to financial learning resources. Moreover, the study emphasizes the need for collaborative efforts among government bodies, educational institutions, and private sectors to develop tailored and inclusive financial literacy initiatives. By addressing these challenges, Indonesia can foster economic empowerment, enhance personal financial well-being, and contribute to sustainable economic development. This paper contributes to the ongoing dialogue on financial education and serves as a foundation for policymakers, educators, and researchers aiming to promote financial literacy as a cornerstone of societal progress.